A Case of Malakoplakia Mimicking Prostatic Malignancy - Kale, Kshitija M; Padmanabhan, Anitha; Acharya, Prapti; Gadgil, Nitin M (Annals of Pathology and Laboratory Medicine, 2020)
Malakoplakia is a granulomatous inflammatory condition commonly involving the urogenital tract. Principally it involves the urinary bladder, prostate is a rare site. Clinical and radiological examination sometimes mimics malignancy. Histology remains confirmatory modality for the diagnosis. Hereby we report a case of prostatic malakoplakia in an elderly male who presented with lower urinary tract symptoms in the past fifteen days. Urine routine microscopy showed pus cells; culture report was positive for E. coli. Serum Prostate Specific antigen (PSA) was 4.6 ug/ml. Magnetic Resonance Imaging (MRI) showed a bulky prostate. A 12-core biopsy was done to rule out malignancy and the histopathology showed benign prostatic glands and the stroma with a predominant population of epithelioid histiocytes and the characteristic Michealis-Gutmann bodies. After a course of antibiotic Nitrofurantoin, transrectal ultrasound was repeated which showed reduction in the prostatic volume. Subsequently Trans-Urethral Resection of Prostate (TURP) was done to relieve the persistent lower urinary tract symptoms. Histology showed similar features. Special stains – Von kossa and Prussian Blue highlighted the Michealis-Gutmann bodies.